1994
DOI: 10.2527/1994.7251119x
|View full text |Cite
|
Sign up to set email alerts
|

Prepartum body condition and weight influences on reproductive performance of first-calf beef cows

Abstract: Data were collected on 476 spring-calving, primiparous cows at six locations in Louisiana over a 2-yr period. Objectives of the study were to evaluate changes in prepartum body condition score (BCS) and BW of heifers when fed varying energy levels and to determine the influences of prepartum BCS and BW changes and BCS at calving on postpartum traits. Heifers were allocated to one of three energy levels from approximately 90 d prepartum to parturition. The diets were formulated to provide low, recommended, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 25 publications
6
51
2
6
Order By: Relevance
“…Results of the present study agree with those of other studies (Osoro and Wright 1992;DeRouen et al 1994;Morrison et al 1999). Although animal scientists and veterinarians use BCS more often than BW in their routine work, this study indicated that BW is the most appropriate indicator of body energy reserves and re-breeding performance of Bos indicus beef cows under extensive production systems in sub-tropic conditions.…”
Section: Resultssupporting
confidence: 82%
“…Results of the present study agree with those of other studies (Osoro and Wright 1992;DeRouen et al 1994;Morrison et al 1999). Although animal scientists and veterinarians use BCS more often than BW in their routine work, this study indicated that BW is the most appropriate indicator of body energy reserves and re-breeding performance of Bos indicus beef cows under extensive production systems in sub-tropic conditions.…”
Section: Resultssupporting
confidence: 82%
“…Capital breeders are expected to invest in reproduction only after enough body reserves (the capital) have been accumulated to reach a "body-condition threshold" (sensus Stearns, 1992). Although the influence of body condition on reproduction has been demonstrated in many species (Albon, Mitchell, Huby, and Brown, 1986;Reznick and Braun, 1987;DeRouen, Franke, Morisson, et al, 1994;Festa-Bianchet, Gaillard, and Jorgenson, 1998), the no-tion of a condition threshold stricto sensu is far less clear (review in Naulleau and Bonnet, 1996;Bonnet et al, 1998b). Our experimental data demonstrate the coexistence of two contrasting reproductive systems within a single capital-breeding snake species: a clearcut condition threshold in females versus a flexible system in males.…”
Section: Discussionmentioning
confidence: 58%
“…É conhecido o efeito negativo da mamada sobre o ciclo estral em vacas de corte (MALVEN, 1984;WHISNANT;KISER;THOMPSON, 1986), determinando anestro pós-parto em função da inibição da secreção de GnRH por opióides endógenos (encefalinas, endorfinas e dinorfinas), o que se torna mais grave em fêmeas com deficiências nutricionais (BUSTAMANTE et al, 1997) e o escore de condição corporal (ECC) baixo, dentre outros fatores que influenciam a duração do anestro (BARUSELLI et al, 2002;MARQUES et al, 2003) contribuindo para baixos índices reprodutivos (RIGOLON et al, 2008 PERKINS, 1999;DEROUEN et al, 1994;LAKE et al, 2005;FONTOURA JUNIOR et al, 2009). …”
Section: Introductionunclassified